2023
DOI: 10.1161/strokeaha.122.040798
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sDPP4 (Soluble Dipeptidyl Peptidase-4) and Cognitive Impairment After Noncardioembolic Acute Ischemic Stroke

Abstract: Background: DPP4 (dipeptidyl peptidase-4) inhibitors have been proven to promote neuronal regeneration, reverse the development of cognitive deficits. However, the association of circulating soluble form (sDPP4 [soluble DPP4]) with poststroke cognitive impairment (PSCI) is unclear. We aimed to investigate the association between plasma sDPP4 levels and PSCI in patients with ischemic stroke. Methods: A total of 600 noncardioembolic stroke patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In those with preexisting dementia pathology, stroke may accelerate existing neurodegeneration. The association between sDPP4 and PSCI observed by You et al 4 was hypothesized to be related to the observed relationship between inhibition of DPP4 and low amyloid burden. The hypothesized pathway between higher sDPP4 and reduced PSCI was based on human cohort studies and animal studies suggesting an inverse relationship between DPP4 activity and concentrations of sDPP4.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…In those with preexisting dementia pathology, stroke may accelerate existing neurodegeneration. The association between sDPP4 and PSCI observed by You et al 4 was hypothesized to be related to the observed relationship between inhibition of DPP4 and low amyloid burden. The hypothesized pathway between higher sDPP4 and reduced PSCI was based on human cohort studies and animal studies suggesting an inverse relationship between DPP4 activity and concentrations of sDPP4.…”
mentioning
confidence: 91%
“…DPP4 inhibitors have also recently emerged as a therapeutic agent of interest for trials of dementia prevention, possibly by reducing amyloid β peptide burden and tau phosphorylation. 3 In a recent study by You et al, 4 the authors demonstrated an association between high levels of the circulating sDPP4 and lower risk of PSCI in patients with a first ever noncardioembolic acute ischemic stroke. The results indicate a dual potential: the identification of a novel molecular biomarker to identify those at risk of PSCI, and a future mechanism for developing therapeutic treatments through an enhanced understanding of the pathogenesis of PSCI.…”
mentioning
confidence: 96%